Keseimbangan Antara Penggunaan Dan Pelestarian Tanah: Degradasi Lahan di Desa Sekaroh Kecamatan Jrowaru, Lombok Timur - Saimah, Wardatun; Sarjan, Muhammad (Lamda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2024)
This research focuses on the balance between land use and land preservation, with a case study of land degradation in Sekaroh Village, Jrowaru District, East Lombok. Land degradation in this area is triggered by changes in land use, unsustainable agricultural practices, and a lack of effective conservation policies. This study employs a qualitative approach using a literature review to explore the factors influencing land degradation, the resulting socio-economic impacts, and community empowerment efforts in land rehabilitation. The findings reveal that land degradation not only threatens environmental sustainability but also reduces the welfare of local communities reliant on agriculture. Through community empowerment, as implemented in the critical forest and land rehabilitation programs in Sekaroh Village, conservation efforts can be carried out by actively involving communities in ecosystem preservation. This participatory approach is deemed effective in achieving a balance between land use for economic purposes and environmental preservation efforts. Recommendations include the adoption of sustainable agricultural practices such as agroforestry, soil conservation, and the provision of education and training to local communities. Policies supporting land conservation and economic incentives to promote environmental preservation are also considered important. Thus, a sustainable balance between land use and preservation can be achieved.